Windows of opportunity in desert ecosystems: Their implications to fungal community development - J. C. Zak; Sinsabaugh, R.; William P. MacKay (Canadian Journal of Botany, 1995)
At the ecosystem level, all fungal activity in arid and semiarid systems is water regulated. However, as the observation scale is changed to allow for finer resolution of moisture effects, one finds that fungal community development in deserts may be influenced by either the temporal patterning of moisture pulses, or biotic factors that extend the benefits of moisture windows. When selected biocides were applied to the root region of a desert bunchgrass, Erioneuron pulchellum, to reduce microarthropod and nematode densities, fungal species numbers associated with the root surface were not altered. The temporal pattern in species numbers apparently reflect large scale seasonal responses of the fungi, microfauna, and plants to yearly differences in the occurrences of moisture windows. For wood on the soil surface, moisture windows of short duration coupled with high temperatures restrict fungal species composition in this habitat resulting in a lack of turnover in the dominant fungal species on surface wood. However, when wood was placed in the more amenable environment of a woodrat midden, patterns of fungal community development differed significantly from that observed for wood on the soil surface. These studies indicate that our understanding of the roles of fungi in the functioning of desert ecosystems is biased because the scale at which we usually make observations is too large to account for abiotic and biotic influences on fungal activity and community development. Moreover, we have to realize that the occurrence of favorable habitats for fungi in arid systems varies considerably in space and time. One consequence of the high spatial and temporal heterogeneity in favorable habitats is that functional diversity among fungi may be greater than would be predicted based solely on abiotic considerations. Key words: deserts, environmental heterogeneity, functional diversity, scale, wood.
Keywords: article; articles; community, fungal; ecosystem, fungal community; fungal community; journal; journals

Interactions among soil biota in desert ecosystems - J. C. Zak; Walter G. Whitford (Agriculture, Ecosystems and Environment, 1988)
In desert systems, the availability of soil nitrogen can be the single most limiting factor controlling plant growth during periods of adequate soil moisture. Decomposition and nitrogen-mineralization rates prior to or during peak periods of plant growth can therefore be critical. Decomposition rates in deserts are generally high, and are relatively independent of rainfall. These high rates can be attributed to a combination of abiotic weathering, the types of microflora and microfauna associated with plant litter, and the adaptation of the soil biota to moisture pulses. The factors controlling litter decomposition and subsequent nitrogen mineralization are dependent upon the location of the organic matter in the habitat. The breakdown of surface litter occurs primarily through either abiotic weathering or by termite consumption. Microarthropods do not appear to have any role in the decomposition of surface litter owing to abiotic constraints on activity. The decomposition of roots, and buried litter, however, has been shown to be dependent on the presence of soil microarthropods. Microbial-microfaunal activity in the root region of desert plants may also have a significant effect on the short-term cycling of nitrogen in arid systems.
Keywords: article; articles; decomposition, abiotic factors; decomposition, microarthropods; decomposition, termites; decomposition, wood-rat middens; journal; journals; microarthropod,decomposition; nitrogen mineralization; rhizosphere; soil biota; termite,decomposition

The occurrence of hypogeous ascomycete in the northern Chihuahuan Desert - J. C. Zak; Walter G. Whitford (Mycologia, 1986)
Sporocarps of the hypogeous ascomycete Carbomyces emergens Gilky were collected in the northern Chihuahuan Desert, at the entrance to the Jornada Experimental Range, 25 km NNE of Las Cruces, New Mexico on March 13, 1985. The site consisted of coppiced dunes vegetated with Atriplex canescens (Pursh) Nutt., Prosopis glandulosa Torr., and several spring flowering annuals, Lepidium lasiocarpum Nutt., and Les- querella gordonii (Gray) Wats. The interdune spaces were generally devoid of vegetation. The ascocarps were discovered 2-5 cm below the soil surface in and around recent rodent digs located in the interdune areas. Dried specimens were subsequently discovered on the soil surface (April 10, 1985) in the ecotone between the Larrea tri- dentata (DC.) Cov. and the Bouteloua eriopoda (Torr.) Torr. vegetation zones of the Jorada Long Term Ecological Research site, located on the New Mexico State University college ranch, 15 km north of the original collection area. Ascocarps (FIG. 1) were subglobose, ovoid to irregular (0.5-2.1 x 0.8-2.0 cm diam), cream to honey yellow in color, and produced singularly and in clusters. Glebal mass was white when immature becoming yellowish brown with the mat- uration of the fertile pockets of asci. Flesh of mature specimens turning yellow when cut, otherwise remaining white at maturity. Dried specimens found on the soil surface were as described by Trappe (1979).
Keywords: article; articles; ascomycetes,hypogeous; Carbomyces; fungi, Carbomyces; fungi, hypogeous ascomycetes; journal; journals